Bully Prevention - Kevin John Bailey; Hector Rios (Networks: An Online Journal for Teacher Research, 2005)
The purpose of this paper is to share with those interested parties the results of my action research study, which is how best to prevent bullying and promote prosocial interaction among a group of eighth grade students attending an elementary school located on the northeast coast of the United States. The study sprang from the need to increase the children's prosocial behaviors and state and federal mandates that require schools to address the problem of bullying in schools.